The promotion of healthy breakfast and snacks based on the social marketing model: a mixed-methods study - Firoozeh Mostafavi (Journal of Health, Population and Nutrition, 2021)
Abstract Background Skipping breakfast and replacing it with non-nutritious snacks are progressively increasing among adolescents. This study aimed to develop an educational intervention based on the Social Marketing Model and evaluate its effects on healthy breakfast and snack consumption among female adolescent students. Methods This mixed-methods study was conducted in 2016–2019 in two phases. In the first phase, a qualitative study was conducted through directed content analysis in guidance schools in Khorramabad, Isfahan, and Tehran, Iran, to explore factors affecting breakfast consumption. The results of this phase were set in the benchmarks of the Social Marketing Model. In the second phase, a randomized controlled trial was conducted based on the benchmarks of the Social Marketing Model on 94 students randomly recruited from guidance schools in Khorramabad, Iran. Results The findings of the qualitative phase were categorized into the benchmarks of the Social Marketing Model, namely the social marketing mix, the intended behavior, internal and external competing factors for behavior modification, theoretical concepts related to the behavior, and the role of supporters. In the quantitative phase, the univariate analysis showed significant between-group differences concerning the product, price, promotion, and behavior (p < 0.05). Conclusion Healthy breakfast and snack consumption can be promoted through making acceptable the tastes, costs, preparations, and consumption places of breakfast and snack. Trial registration The trial was registered in the Iranian Registry of Clinical Trials (code: IRCT20170201032347N1 ). The trial was registered in 11/07/2018 and is accessible on the Iranian Clinical Trial Registration website.